EFISIENSI PENERAPAN UU ITE TERHADAP PELAKU TINDAK PIDANA PERJUDIAN ONLINE (STUDI KASUS PUTUSAN NOMOR 277/PID.B./2018/PN.SBR.) (Lex Jurnalica, 2019)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Abstract Online Gambling activity is a cybercrime which must be regulated in a specific legislation, so that it has become a principle of legality. In law, there is a principle that reads